2011
DOI: 10.1073/pnas.1101360108
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule depolymerization in Caenorhabditis elegans touch receptor neurons reduces gene expression through a p38 MAPK pathway

Abstract: Microtubules are integral to neuronal development and function. They endow cells with polarity, shape, and structure, and their extensive surface area provides substrates for intracellular trafficking and scaffolds for signaling molecules. Consequently, microtubule polymerization dynamics affect not only structural features of the cell but also the subcellular localization of proteins that can trigger intracellular signaling events. In the nematode Caenorhabditis elegans , the processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 51 publications
8
78
0
Order By: Relevance
“…The parallel DLK-1 and MLK-1 pathways activating PMK-3(p38) and KGB-1(JNK) may also be relevant to the studies demonstrating a role for DLK in regulating axon degeneration in Drosophilia (30) and microtubule regulated gene expression in C. elegans (44). The model proposed by Bounoutas et al suggests that an unknown MAPKK may activate PMK-3 in parallel to MKK-4 (44).…”
Section: Discussionmentioning
confidence: 99%
“…The parallel DLK-1 and MLK-1 pathways activating PMK-3(p38) and KGB-1(JNK) may also be relevant to the studies demonstrating a role for DLK in regulating axon degeneration in Drosophilia (30) and microtubule regulated gene expression in C. elegans (44). The model proposed by Bounoutas et al suggests that an unknown MAPKK may activate PMK-3 in parallel to MKK-4 (44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, two new alleles of pmk-3, ju1010 and ju592, are nonsense mutations after the kinase domain, suggesting that the C terminus of PMK-3 may regulate the protein activity or stability. cebp-1(ju634) altered arginine 63 to proline in the N terminus of the protein, whereas the majority of the previously reported cebp-1 mutations affect the bZip domain (Yan et al 2009;Bounoutas et al 2011) ( Figure 2D and Table S1). In summary, 98% of the suppressor mutations identified in our screens affected the six genes of the DLK-1 kinase cascade ( Figure 2A and Table S1), and the number of the identified alleles roughly correlated with the size of the coding regions of the genes ( Figure 2B).…”
mentioning
confidence: 87%
“…However, how microtubules coordinate structural stability and remodeling of neurons under insults remains incompletely understood. Genetic or pharmacologic ablation of microtubules in the C. elegans touch neurons reduced the expression of several touch neuron-specific genes through the activation of the DLK-1 MAPK pathway (14). Because DLK-1 is a major effector for neuronal remodeling, taken together, these studies raise the possibility that microtubule disruption drives neuronal remodeling through DLK-1 activation.…”
mentioning
confidence: 91%
“…Genetic or pharmacologic ablation of microtubules in C. elegans activates dlk-1, a MAPKKK (14). It had been reported that rpm-1 mutants, which had high dlk-1 activity, lost PLM branches (30).…”
Section: Dlk-1/mapk Functions Downstream Of Rhgf-1 In Plm Remodeling Onmentioning
confidence: 99%